2019
DOI: 10.1002/cbdv.201900176
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Bioactive Compounds of Traditional Chinese Medicines for Insulin Resistance Based on Signaling Pathways

Abstract: Type 2 diabetes is a serious metabolic disease as a long‐term threat to human health. Insulin resistance is not only the basis and major feature of type 2 diabetes, but also the main etiology of diseases such as hypertension, hyperlipidemia and coronary heart disease. It has been shown that Traditional Chinese Medicines (TCMs) play an important role in the treatment of type 2 diabetes, through attenuating insulin resistance, whereas the mechanism involved is not yet well understood. Therefore, it is important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Traditional Chinese medicine is a valuable therapeutic strategy and drug resource for the treatment of metabolic disorders including metabolic syndrome, type 2 diabetes and insulin resistance (Li et al, 2014;Pan and Kong, 2018;He et al, 2019). However, it is a challenge to explore the active ingredients of traditional Chinese medicine and their potential molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine is a valuable therapeutic strategy and drug resource for the treatment of metabolic disorders including metabolic syndrome, type 2 diabetes and insulin resistance (Li et al, 2014;Pan and Kong, 2018;He et al, 2019). However, it is a challenge to explore the active ingredients of traditional Chinese medicine and their potential molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenosides, as the main active components of ginseng, have a wide range of pharmacological effects ( He et al, 2019 ), including antioxidant ( He, 2017 ; Yang et al, 2018 ), antitumor ( Zhou et al, 2018 ), anti-inflammatory ( Chen et al, 2019 ; He and Li, 2015 ), anti-aging ( Sun et al, 2018 ), etc., among which the antitumor effect is one of the hot spots of research. Many experiments have shown that ginsenosides can inhibit the invasion and metastasis of tumors ( Wu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing research attention has been paid to novel, effective antidiabetes agents derived from natural sources [ 1 ]. Alismatis rhizoma (AR) is the tuber of Alisma orientale (Sam.)…”
Section: Introductionmentioning
confidence: 99%